When regulatory acts containing the civil law norms become effective or lose their effect - O.A. Kuznetsova (Ученые записки Казанского университета: Серия Гуманитарные науки)
For the correct application of regulatory acts containing the civil law norms, it is necessary to define the period of their being in legal force which fits the time between two dates, and in particular between the date of their coming into force and the date when they lose their effect. The purpose of the paper is to demonstrate the problems of establishing the grounds for bringing into force and to termination a civil regulatory act and to propose the possible solutions to the problems. It has been concluded that regardless the way and the method of bringing into force the act containing civil law norms, this act is simultaneously in effect on the territory of the whole country; it regulates civil relations; it can be declared unconstitutional or non-functioning; it can function retroactively (having a reverse action). The grounds for bringing a regulatory act to termination are: declaring the act as the one being no longer in force, the expiration of the period for which the act was originally adopted, annulment of the act, declaring the act unconstitutional or non-functioning, declaring the invalidity of the USSR acts (of the RSFSR acts, of the acts introduced by the RF authorities which ceased to exist). After the act loses its legal force, it ceases to be effective except for the cases of its ultra-active function; it can be only applied to the civil relations which started and were completed before the act stopped to be effective; it cannot anymore be declared unconstitutional or non-functioning except for the cases when it continues to be applied to civil relations. It is feasible to legally allow for an opportunity to contest the civil law acts which have lost their effect if they are not intended for application, including by the reason of their ultra-active function.